Analysis of Digital Marketing Strategy on Product Sales: A Study of PT Ousean Global Digital - Hari Mega Muhtar; Adang Djatnika Effendi; Leni Burhan (JEMBA: Journal of Economics, Management, Business and Accounting, 2023)
This journal article discusses the analysis of digital marketing strategies on product sales of PT Ousean Group. This study was conducted by using the method of observation and documentation. The source of the data comes from the results of observations and company documentation obtained online. This type of data is in the form of good information about the digital marketing strategy used by the company. The data collection technique was carried out by means of observation, namely systematic observation and recording and document technique, namely the collection of previous documents in the form of writing, drawings or monumental works. Data analysis techniques are carried out by interpreting data containing information on the company's digital marketing strategy.